Drug-induced mitochondrial toxicity: Risks of developing glucose handling impairments - Kuretu, Auxiliare; Arineitwe, Charles; Mothibe, Mamosheledi; Ngubane, Phikelelani; Khathi, Andile; Sibiya, Ntethelelo (Frontiers in Endocrinology, 2023)
Mitochondrial impairment has been associated with the development of insulin resistance, the hallmark of type 2 diabetes mellitus (T2DM). However, the relationship between mitochondrial impairment and insulin resistance is not fully elucidated due to insufficient evidence to support the hypothesis. Insulin resistance and insulin deficiency are both characterised by excessive production of reactive oxygen species and mitochondrial coupling. Compelling evidence states that improving the function of the mitochondria may provide a positive therapeutic tool for improving insulin sensitivity. There has been a rapid increase in reports of the toxic effects of drugs and pollutants on the mitochondria in recent decades, interestingly correlating with an increase in insulin resistance prevalence. A variety of drug classes have been reported to potentially induce toxicity in the mitochondria leading to skeletal muscle, liver, central nervous system, and kidney injury. With the increase in diabetes prevalence and mitochondrial toxicity, it is therefore imperative to understand how mitochondrial toxicological agents can potentially compromise insulin sensitivity. This review article aims to explore and summarise the correlation between potential mitochondrial dysfunction caused by selected pharmacological agents and its effect on insulin signalling and glucose handling. Additionally, this review highlights the necessity for further studies aimed to understand drug-induced mitochondrial toxicity and the development of insulin resistance.